Patients Walking Faster After Anterior Cruciate Ligament Reconstruction Have More Gait Asymmetry - Rachel J. Knobel; Naoaki Ito; Elanna K. Arhos; Jacob J. Capin; Thomas S. Buchanan; Lynn Snyder-Mackler (International Journal of Sports Physical Therapy)
# Background Gait asymmetries after anterior cruciate ligament reconstruction (ACLR) may lead to radiographic knee osteoarthritis. Slower walking speeds have been associated with biomarkers suggesting cartilage breakdown. The relationship between walking speed and gait symmetry after ACLR is unknown.